The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4136/ambi-agua.2243
|View full text |Cite
|
Sign up to set email alerts
|

Integration of treatment technologies with Fenton reagent for laboratory effluent remediation

Abstract: This study investigated of the potential value of the integration of the coagulation/flocculation, Advanced Oxidation Processes (AOP) (Fenton reagent) and slow sand filtration technologies, with the aim of treating laboratory wastewater. The treatment system was designed in laboratory scale through coagulation/flocculation. It involved the use of Jar Test equipment with a sequence of two rotational phases: fast mixes to 300 rpm for 20 seconds and slow mixes to 30 rpm for 6 minutes and 10 seconds, with the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The residual iron after the process was between 4.6 to 5.8 mg Fe.L -1 . Pereira and Brito (2018) obtained, at the end of the treatment process for the removal of laboratory effluents, the concentration of residual total soluble iron was 6.40 mg.L -1 . In Figure 6, it is possible to see the difference between the synthetic effluent after the treatment, with a color change due to the presence of the sludge containing the iron, and after it is filtered with a 0.45 µm PTFE filter.…”
Section: Total Iron Residualmentioning
confidence: 96%
See 1 more Smart Citation
“…The residual iron after the process was between 4.6 to 5.8 mg Fe.L -1 . Pereira and Brito (2018) obtained, at the end of the treatment process for the removal of laboratory effluents, the concentration of residual total soluble iron was 6.40 mg.L -1 . In Figure 6, it is possible to see the difference between the synthetic effluent after the treatment, with a color change due to the presence of the sludge containing the iron, and after it is filtered with a 0.45 µm PTFE filter.…”
Section: Total Iron Residualmentioning
confidence: 96%
“…(2020) obtained the greatest removal of Ibuprofen with the optimized values of 110 min and 2 A and drug concentration of 40 ppm. The treatment is enhanced with the addition of H2O2, allowing greater removal of the contaminant in a shorter time (Pereira et al 2018).…”
Section: Global Desirabilitymentioning
confidence: 99%
“…The parameters of treatment time and rotation, as well as the range of initial concentrations of chemical reagents were used for the treatment technology (Fenton´s reagent). It were also based on the values of the parameters used in Pereira and Brito (2018) Morais and Brito (2015), Ma and Xia (2009), and in the wastewater treatment station of Goiânia-GO.…”
Section: Effluent Characterizationmentioning
confidence: 99%
“…Similar experiments were performed by Maharaj et al [7] with synthetic wastewater and observed a maximum COD reduction of 70% at the reaction time of 360 min. Studies were conducted by Perica et al [16] on heterogeneous Fenton in the removal of COD and observed 75% COD removal at 400 min.…”
Section: Fenton Processmentioning
confidence: 99%